2008
DOI: 10.1007/s11664-008-0379-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Carbon Nanotubes on the Shear Strength and Electrical Resistivity of a Lead-Free Solder

Abstract: In this study, the influence of carbon nanotubes (CNTs) on the shear strength and electrical resistivity of 95.8Sn-3.5Ag-0.7Cu lead-free solder was investigated. Composite solders containing various weight percentages of CNTs were synthesized, and electrical resistivity results of the bulk composite solders revealed that the presence of CNTs did not degrade the electrical performance of such solders. Tests conducted on lap-shear solder joint samples showed an improvement in the shear strength of the composite … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
38
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 110 publications
(44 citation statements)
references
References 34 publications
4
38
1
1
Order By: Relevance
“…CNTs and Cu nanoparticles, can form connections on the surface of the nanotubes or from end to end. This is different from the findings of earlier studies, in which connections either involved using bulk nanotubes or occurred on the surface of nanotubes [11,[25][26][27][28]. Fig.…”
contrasting
confidence: 83%
“…CNTs and Cu nanoparticles, can form connections on the surface of the nanotubes or from end to end. This is different from the findings of earlier studies, in which connections either involved using bulk nanotubes or occurred on the surface of nanotubes [11,[25][26][27][28]. Fig.…”
contrasting
confidence: 83%
“…[41,95] Babaghorbani et al studied the electrical properties of nanocomposite solders in detail and reported that nano-sized reinforcements is advantageous in not degrading the electrical conductivity of the device, while micron sized particles can degrade the conductivity values . [96] This further confirms the unique properties of nanocomposite solders for electromigration property microelectronic packaging devices. Recently, it has been demonstrated the nanoparticles reinforced solders can be promising candidates for preventing electromigration failure in electronic packaging devices.…”
Section: Electrical Conductivitysupporting
confidence: 69%
“…In order to solve these problems, efforts have been made to develop new Pb-free solders with a low melting point, good mechanical properties, better microstructure properties, and high creep resistance. Recently, Pb-free solders doped with nano-sized, nonreacting, noncoarsening oxide dispersoids have been identified as potential materials that could provide higher microstructure stability and better mechanical properties than the conventional solders [13][14][15][16][17][18][19][20][21][22][23][24]. Tsao et al [14][15][16] [19] or multi-walled carbon nanotubes [20,21] on the mechanical properties of nano-composite solders.…”
Section: Nano-composite Soldersmentioning
confidence: 99%
“…Tsao et al [14][15][16] [19] or multi-walled carbon nanotubes [20,21] on the mechanical properties of nano-composite solders. The data on the enhancement of the mechanical properties of nano-composite solders collected from some of the literature are listed in Table 2 [13,14,16,22,23]. Here, it should be stressed that although the addition of nanoparticles into solder matrices can improve the creep behavior [24], the effects on the corrosion resistance and mechanical properties of the nano-composite solders cannot be ignored.…”
Section: Nano-composite Soldersmentioning
confidence: 99%